2017
DOI: 10.3389/fcimb.2017.00201
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Limits Uptake of Listeria monocytogenes by Macrophages to Reduce the Intracellular Niche and Control Infection

Abstract: MiRNAs are important post-transcriptional regulators of gene expression. MiRNA expression is a crucial part of host responses to bacterial infection, however there is limited knowledge of their impact on the outcome of infections. We investigated the influence of miR-21 on macrophage responses during infection with Listeria monocytogenes, which establishes an intracellular niche within macrophages. MiR-21 is induced following infection of bone marrow-derived macrophages (BMDMs) with Listeria. MiR-21−/− macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…To promote host cell entry, numerous pathogens utilize cholesterol-rich microdomains known as lipid rafts, which serve as organizational and functional platforms for host signaling pathways involved in phagocytosis [37]. Although Shigella and Listeria are cytosolic pathogens, their nutritional adaptation to the host cytosol is distinct and they manipulate unique host processes to obtain nutrients [39][40][41][42], and ABC transporter are detrimental to disease manifestation [43]. Coxiella resides within phagolysosomes, which is a rich resource for host nutrients [44,45].…”
Section: How Intracellular Pathogens Overcome Host Nutrient Restrictionmentioning
confidence: 99%
“…To promote host cell entry, numerous pathogens utilize cholesterol-rich microdomains known as lipid rafts, which serve as organizational and functional platforms for host signaling pathways involved in phagocytosis [37]. Although Shigella and Listeria are cytosolic pathogens, their nutritional adaptation to the host cytosol is distinct and they manipulate unique host processes to obtain nutrients [39][40][41][42], and ABC transporter are detrimental to disease manifestation [43]. Coxiella resides within phagolysosomes, which is a rich resource for host nutrients [44,45].…”
Section: How Intracellular Pathogens Overcome Host Nutrient Restrictionmentioning
confidence: 99%
“…It has been shown that miR‐21 is induced in response to infection of macrophages with L . monocytogenes and regulates the phagocytosis rate to limit the intracellular niche of the pathogen . miR‐21 also plays a role in hematopoietic cells hemostasis during atherogenesis.…”
Section: Role Of Mirnas In Innate Immunitymentioning
confidence: 99%
“… SUPPORTING CITATIONS The following references appear in the Supplemental Information: Afonso et al (2018); Ahmed et al (2011); Chen et al (2016); Fiorentino et al (2013); Hatley et al (2010); He et al (2016); Hu et al (2008); Hu et al (2017); Johnston et al (2017); Kölling et al (2017); Li et al (2013); Liang et al (2012); Liu et al (2011); Lorenzen et al (2015); Lu et al (2008); Lu et al (2009); Luo et al (2014); Marquez et al (2010); McDonald et al (2013); Ng et al (2012); Roy et al (2009); Ruan et al (2014); Sawant et al (2013); Sayed et al (2008); Sayed et al (2010); Shi et al (2013); Singh et al (2015); Soares et al (2014); Song et al (2010); Sugatani et al (2011); Thum et al (2008); Wang et al (2013); Wang et al (2015); Wang et al (2016); Wu et al (2012); Wu et al (2015); Xie et al (2016); Yang et al (2011); Yang et al (2018); Ye et al (2014). …”
mentioning
confidence: 99%